BV-2 Microglial Cells Overexpressing C9orf72 Hexanucleotide Repeat Expansion Produce DPR Proteins and Show Normal Functionality but No RNA Foci - Rostalski, Hannah; Hietanen, Tomi; Leskelä, Stina; Behánová, Andrea; Abdollahzadeh, Ali; Wittrahm, Rebekka; Mäkinen, Petra; Huber, Nadine; Hoffmann, Dorit; Solje, Eino; Remes, Anne M.; Natunen, Teemu; et al. (Frontiers in Neurology, 2020)
Hexanucleotide repeat expansion (HRE) in the chromosome 9 open-reading frame 72 (C9orf72) gene is the most common genetic cause underpinning frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). It leads to the accumulation of toxic RNA foci and various dipeptide repeat (DPR) proteins into cells. These C9orf72 HRE-specific hallmarks are abundant in neurons. So far, the role of microglia, the immune cells of the brain, in C9orf72 HRE-associated FTLD/ALS is unclear. In this study, we overexpressed C9orf72 HRE of a pathological length in the BV-2 microglial cell line and used biochemical methods and fluorescence imaging to investigate its effects on their phenotype, viability, and functionality. We found that BV-2 cells expressing the C9orf72 HRE presented strong expression of specific DPR proteins but no RNA foci. Transiently increased levels of cytoplasmic TAR DNA-binding protein 43 (TDP-43) but no signs of cell death were detected in HRE overexpressing cells. Overexpression of the C9orf72 HRE did not affect BV-2 cell phagocytic activity or response to an inflammatory stimulus, nor did it shift their RNA profile towards disease-associated microglia. These findings suggest that DPR proteins do not affect microglial cell viability or functionality in BV-2 cells. However, additional studies in other models are required to further elucidate the role of C9orf72 HRE in microglia.